Antibiotic Resistance and Virulence Traits in Vancomycin-Resistant Enterococci (VRE) and Extended-Spectrum β-Lactamase/AmpC-producing (ESBL/AmpC) Enterobacteriaceae from Humans and Pets - Ramona Iseppi; Alessandro Di Cerbo; Patrizia Messi; Carla Sabia (MDPI AG, 2020)
Background: We investigated the virulence factors, genes, antibiotic resistance patterns, and genotypes (VRE and ESBL/AmpC) production in Enterococci and Enterobacteriaceae strains isolated from fecal samples of humans, dogs, and cats. Methods: A total of 100 fecal samples from 50 humans, 25 dogs, and 25 cats were used in the study. MICs of nine antimicrobials were determined using the broth microdilution method. Polymerase chain reaction was used for the detection of genes responsible for antibiotic resistance (VRE and ESBL/AmpC) and virulence genes both in Enterococcus species, such as cytolysin (cylA, cylB, cylM), aggregation substance (agg), gelatinase (gelE), enterococcal surface protein (esp), cell wall adhesins (efaAfs and efaAfm), and in Enterobacteriaceae, such as cytolysin (hemolysin) and gelatinase production (afa, cdt, cnf1, hlyA, iutA, papC, sfa). Results: Enterococcus faecium was the most prevalent species in humans and cats, whereas Enterococcus faecalis was the species isolated in the remaining samples. A total of 200 Enterobacteriaceae strains were also detected, mainly from humans, and Escherichia coli was the most frequently isolated species in all types of samples. In the Enterococcus spp, the highest percentages of resistance for ampicillin, amoxicillin/clavulanate, erythromycin, tetracycline, ciprofloxacin, teicoplanin, and vancomycin were detected in cat isolates (41.6%, 52.8%, 38.9%, 23.6%, 62.5%, 20.8%, and 23.6% respectively), and in E. coli, a higher rate of resistance to cefotaxime and ceftazidime emerged in cat and dog samples, if compared with humans (75.4% and 66.0%, 80.0% and 71.4%, and 32.0% and 27.2%, respectively). Regarding the total number of enterococci, 5% and 3.4% of the strains were vancomycin and teicoplanin resistant, and the vancomycin resistance (van A) gene has been detected in all samples by PCR amplification. All the Enterobacteriaceae strains were confirmed as ESBL producers by PCR and sequencing, and the most frequent ESBL genes in E. coli strains from humans and pet samples were blaCTX-M-1 and blaCTX-M-15. Conclusions: Our results provide evidence that one or more virulence factors were present in both genera, underlining again the ability of pet strains to act as pathogens.